Urban Heat Island and its effect on Dweller of Kolkata Metropolitan area using Geospatial Techniques - Gazi, Md Amir Ali; Mondal, Ismail (International Journal of Computer Sciences and Engineering, 2025)
The significance of Urban heat island (UHI) is to space heater than the urban adjacent area. This heat energy creates by urban people, house, shops, cars, buses, trains, industrial zone, etc. The UHI be an vital occurrence of urban environment in addition to gives direct and circumlocutory effect lying on urban population. In UHI calculating using landsat thermal band, Landsat TM, ETM+ and OLI satellite image (2000, 2008, 2017 Year) data processed to obtain a atmoshphire window method use to retrieve the land surface temperature (LST) using specifically band-6 (TM, ETM+) and band 10 (OLI) for data procurement and investigation. UHI consequence related with rising impermeable surface both spatially and temporally. This study aims to analyze the changes in LST with advent of the Kolkata Metropolitan Area (KMA). The result found that the (LST) is increasing sharply. The mean temperature of the area was 22.33°C in 2000 which became 23.68°C in 2008 and 23.79°C in 2017. The relation of built-up (NDBI) and LST is found positively correlated with a r value of 0.96 in 2000 and 0.78in 2017 and the relation with vegetation (NDVI) is negatively related and the r value is -0.98 in the years of 2000 and the r value is -0.97 in 2017, several heat zones are highlight and have been identified on the map of the KMA area. The addition of Geospatial technology be set up in the direction of valuable in monitor and analyze urban expansion pattern and in evaluation urbanization collision on surface temperature. Finally, the study suggests considering the possible micro-climatic changes in Kolkata metropolitan area and planning for the sustainable improvement